Mirror emissivity measurements for the NASA AURA HIRDLS instrument - Barnett, J; Djotni, K; Hepplewhite, C; Oduleye, O; Palmer, C; Peters, D; Walton, T; Watkins, R; Whitney, J; Gille, J; Arter, P; Nardi, B (2003)
The High Resolution Dynamics Limb Sounder (HIRDLS) instrument is scheduled for launch on the NASA AURA satellite in January 2004; it is a joint project between the UK and USA. HIRDLS is a mid-infrared limb emission sounder which will measure the concentrations of trace species and aerosol, and temperature and pressure variations in the Earth's atmosphere between about 8 and 100 km altitude on a finer spatial scale than been achieved before. HIRDLS has particularly stringent radiometric calibration accuracy requirements. A warm (280-300K) 'In-Flight Calibrator' (IFC) black cavity within the instrument plus a view to cold space are used to perform radiometric calibration. The cavity has an entrance aperture which is much smaller than the full beam size, and it is viewed through a focusing mirror. The cavity and focusing mirror are ideally maintained at the same temperature but differences of up to 1 C may exist, in which case a correction utilising the mirror emissivity can usefully be made. That emissivity has been measured at instrument level during pre-launch calibration by viewing an external target at the same temperature as the IFC while varying the calibration mirror temperature.